Climate risk management through sustainable land and water management in Sub-Saharan Africa - Nkonya, Ephraim M.; Koo, Jawoo; Kato, Edward; Johnson, Timothy (Food and Agriculture Organization of the United Nations, 2018)
Weather volatility is increasing, hence the need to build resilience for farmers and the poor, who are affected the most. Using Mali and Nigeria as case study countries, this study shows that climate change may reduce the yield of staple food crops – namely maize, rice, and millet – by 20% in 2050 compared to their levels in 2000. Sustainable land and water management (SLWM) – which includes a combination of organic soil fertility, inorganic fertilizer, and water managements – will more than offset the effect of climate change on yield under the current management practices. Additionally, SLWM is more profitable and could therefore increase household income and address poverty. Unfortunately, adoption rates of SLWM remain low. Policies and strategies for increasing their adoption includes improvement of market access, enhancing the capacity of agricultural extension service providers to provide advisory services on SLWM, and building an effective carbon market that involves both domestic and international buyers. The recent United Nations Framework Convention on Climate Change (UNFCCC) provides one of the opportunities for reducing climate risks and achieving sustainable agricultural production under climate change.